2018
DOI: 10.3390/atmos9110434
|View full text |Cite
|
Sign up to set email alerts
|

Non-Monotonic Dependencies of Cloud Microphysics and Precipitation on Aerosol Loading in Deep Convective Clouds: A Case Study Using the WRF Model with Bin Microphysics

Abstract: Aerosol-cloud-precipitation interactions in deep convective clouds are investigated through numerical simulations of a heavy precipitation event over South Korea on 15–16 July 2017. The Weather Research and Forecasting model with a bin microphysics scheme is used, and various aerosol number concentrations in the range N0 = 50–12,800 cm−3 are considered. Precipitation amount changes non-monotonically with increasing aerosol loading, with a maximum near a moderate aerosol loading (N0 = 800 cm−3). Up to this opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…This value marks the turning point from invigoration to suppression in the trend. Such nonmonotonic dependence suggests competition between at least two dominant processes 34,35 . However, before investigating aerosol-related processes, we explored the possible influence of meteorology on both aerosols and clouds that can produce apparent correlations with no real causality 36 .…”
Section: Resultsmentioning
confidence: 99%
“…This value marks the turning point from invigoration to suppression in the trend. Such nonmonotonic dependence suggests competition between at least two dominant processes 34,35 . However, before investigating aerosol-related processes, we explored the possible influence of meteorology on both aerosols and clouds that can produce apparent correlations with no real causality 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent numerical modelling studies show that the relationship between precipitation amount and aerosol loading is not monotonic (Jeon et al ., 2018; Lkhamjav et al ., 2018). The amount of precipitation from deep convective clouds slightly decreases as aerosol loading increases in a certain range of concentration, while notably increases in a higher concentration range.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Changes in hydrometer concentration and size distribution were shown to affect clouds' microphysical process rates (such as condensation, evaporation, freezing and collision-coalescence), which in turn could affect the dynamics of the clouds (Khain et al, 2005;Koren et al, 2005;Heikenfeld et al, 2019;Chen et al, 2017;Seifert and Beheng, 2006a), the rain production (Levin and Cotton, 2009;Albrecht, 1989;Tao et al, 2012) and the clouds' radiative effect (Koren et al, 2010;Storelvmo et al, 2011;Twomey, 1977;Albrecht, 1989). The aerosol effect, and in particular its effects on the radiation budget and the atmospheric energy budget, is dependent on cloud regime Lee et al, 2009;Mülmenstädt and Feingold, 2018;van den Heever et al, 2011;Rosenfeld et al, 2013;Glassmeier and Lohmann, 2016;Gryspeerdt and Stier, 2012;Christensen et al, 2016), time (Dagan et al, 2017(Dagan et al, , 2018cGryspeerdt et al, 2015;Seifert et al, 2015;Lee et al, 2012), aerosol type and size distribution (Jiang et al, 2018;Lohmann and Hoose, 2009), and (even for a given cloud regime) meteorological conditions (Dagan et al, 2015a;Fan et al, 2009Fan et al, , 2007Kalina et al, 2014;Khain et al, 2008) and was shown to be non-monotonic (Dagan et al, 2015b;Jeon et al, 2018;Gryspeerdt et al, 2019;Liu et al,...…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike in the deep-cloud case, the mean effect on precipitation, under typical modern-day conditions, is thought to be negative (Albrecht, 1989;Rosenfeld, 2000;Jiang et al, 2006;Xue and Feingold, 2006;Dagan and Chemke, 2016). The aerosol effect on shallow cloud cover and mean water mass (measured by liquid water path -LWP) might also depend on the meteorological conditions and aerosol range (Dagan et al, 2015b(Dagan et al, , 2017Dey et al, 2011;Savane et al, 2015) and is the outcome of competition between different opposing responses of rain suppression (that could lead to an increase in cloud lifetime and coverage; Albrecht, 1989), warm cloud invigoration (that could also lead to an increase in cloud coverage and LWP; Koren et al, 2014;Kaufman et al, 2005; al., 2011b), and an increase in entrainment and evaporation (that could lead to a decrease in cloud coverage; Small et al, 2009;Jiang et al, 2006;Costantino and Bréon, 2013;Seigel, 2014). Another addition to this complex response is the fact that the aerosol effect on warm convective clouds was shown to be time-dependent and affected by the clouds' feedbacks on the thermodynamic conditions (Seifert et al, 2015;Dagan et al, , 2017Dagan et al, , 2018bLee et al, 2012;Stevens and Feingold, 2009).…”
Section: Introductionmentioning
confidence: 99%